'Information Aid' and the Dissemination of Innovation. Issue 1 (27th March 2013) - Milius, Djims
<x xml:space="preserve">Abstract</x> DjimsMilius responds to the article 'Intellectual Property, Dissemination of Innovation and Sustainable Development' by Claude Henry and Joseph Stiglizt, published by Global Policy in 2010. Milius emphasises the international legislative reforms proposed by the original paper to clarify the terms of intellectual property. But he remains dissatisfied with the authors' approach to dissemination and recommends a policy of 'information aid' as a remedial tool for this purpose.<boxed-text content-type="graphic" id="f1ga" position="anchor" orientation="portrait"> </boxed-text>